2013
DOI: 10.3109/13880209.2013.853813
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of the main individual phenolics and juglone in walnut (Juglans regia) leaves

Abstract: Context: Walnut [Juglans regia L. (Juglandaceae)] is a rich source of phenolic compounds, including phenolic acids, naphtoquinones and flavonoids. The increasing interest in the powerful biological activities of plant phenolics has outlined the necessity of determining their content in leaves of different walnut cultivars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 35 publications
1
46
0
4
Order By: Relevance
“…Lately, juglone (Jug), a natural plant product extracted from green walnut husks of Juglans mandshurica, a deciduous tree widely cultivated in India, China and Indochina, has displayed potential anti-mycobacterials activity and antitumor activity [19]. Juglone as an important source of naphthoquinone drugs, the fruits have been widely used in folkloric statement of China for the precaution of various human diseases, including cancer, stomach pain and angiocardiopathy [19,20]. However, there are no related reports about the anti-inflammatory effect of juglone and its mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, juglone (Jug), a natural plant product extracted from green walnut husks of Juglans mandshurica, a deciduous tree widely cultivated in India, China and Indochina, has displayed potential anti-mycobacterials activity and antitumor activity [19]. Juglone as an important source of naphthoquinone drugs, the fruits have been widely used in folkloric statement of China for the precaution of various human diseases, including cancer, stomach pain and angiocardiopathy [19,20]. However, there are no related reports about the anti-inflammatory effect of juglone and its mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have found that the total phenolic content of the walnut leaves presented seasonal fluctuation and concluded that they should preferentially be collected in July, when the phenolics content is higher (Cosmulescu & Trandafir 2011;Jalili & Sadeghzade 2012;Cosmulescu et al 2014). Fresh walnut leaves were picked randomly in mid-July from different parts of three walnut trees grown in the experimental field of Banu Maracine Didactical Station of University of Craiova, located in the region of Oltenia, Romania (44 20 0 N, 23 49 0 E).…”
Section: Plant Tissuementioning
confidence: 99%
“…Based on these traditional uses and from the wide availability of walnut leaves in abundant amounts, numerous studies have been conducted in recent years related to the content of the leaves in bioactive compounds, their antioxidant and antiseptic properties, in order to justify, at least partially, their therapeutic uses (Pereira et al 2007;Almeida et al 2008;Amaral et al 2008;Carvalho et al 2010;Cosmulescu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As expressed by many authors [58,59], composition of the phenolics, and among them also phenolic acids, depends on both environmental conditions (temperature, humidity, exposure to light) and biological influences (e.g., insects and herbivores) [60]. Tytanit and its active component, Ti 4+ ions, were investigated previously, and their effect on biomass production and condition of plants was confirmed [42,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%